Inheriting Dance's Alternative Histories. (25th June 2014) - Elswit, Kate
<x content-type="archive" xml:space="preserve">Abstract</x> In 1975, German choreographer Kurt Jooss created his last dance, Dixit Dominus, for Swedish-based Indian dancer Lilavati Häger. After Rani Nair reconstructed what is often seen as a "minor" work, she then created Future Memory (2012) to engage more directly with her inheritance, from caring for the personal things and stories that surrounded the piece to re-working its promise of dancing between European and Indian forms. Working outward from my position as dramaturg and historian for this project, this essay addresses the potential and precariousness of contemporary dance's experiments with redoing history at the intersection of multiple contested legacies.